Facial expression movement enhances the measurement of temporal dynamics of attentional bias in the dot-probe task. (August 2017) - Caudek, Corrado; Ceccarini, Francesco; Sica, Claudio
Abstract: The facial dot-probe task is one of the most common experimental paradigms used to assess attentional bias toward emotional information. In recent years, however, the psychometric properties of this paradigm have been questioned. In the present study, attentional bias to emotional face stimuli was measured with dynamic and static images of realistic human faces in 97 college students (63 women) who underwent either a positive or a negative mood-induction prior to the experiment. We controlled the bottom-up salience of the stimuli in order to dissociate the top-down orienting of attention from the effects of the bottom-up physical properties of the stimuli. A Bayesian analysis of our results indicates that 1) the traditional global attentional bias index shows a low reliability, 2) reliability increases dramatically when biased attention is analyzed by extracting a series of bias estimations from trial-to-trial (Zvielli, Bernstein, & Koster, 2015), 3) dynamic expression of emotions strengthens biased attention to emotional information, and 4) mood-congruency facilitates the measurement of biased attention to emotional stimuli. These results highlight the importance of using ecologically valid stimuli in attentional bias research, together with the importance of estimating biased attention at the trial level. Highlights: An attentional bias index is computed using RTs derived from the dot-probe task. Dynamic expression of emotions strengthens biased attention to emotional information. Importance of using ecologically valid stimuli in dot-probe research. The temporal dynamics of the attentional bias must be taken into account.